Collaboration in supply chain management: A resilience perspective - Ruth Banomyong (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
This paper investigates how collaboration between stakeholders can help make supply chains more resilient. It explores innovative ways to operate supply chains and reinforce their resilience, for instance through crowd shipping or gainsharing. The paper also includes a case study on how multi-stakeholder initiatives and public-private partnership can help foster collaboration in supply chains for increased efficiency.
Keywords: 330